The role of coagulation and platelets in colon cancer-associated thrombosis - Mitrugno, Annachiara (Am J Physiol Cell Physiol, 2019)
Cancer-associated thrombosis is a common first presenting sign of malignancy and is currently the second leading cause of death in cancer patients after their malignancy. However, the molecular mechanisms underlying cancer-associated thrombosis remain undefined. In this study, we aimed to develop a better understanding of how cancer cells affect the coagulation cascade and platelet activation to induce a prothrombotic phenotype. Our results show that colon cancer cells trigger platelet activation in a manner dependent on cancer cell tissue factor (TF) expression, thrombin generation, activation of the protease-activated receptor 4 (PAR4) on platelets and consequent release of ADP and thromboxane A2. Platelet-colon cancer cell interactions potentiated the release of platelet-derived extracellular vesicles (EVs) rather than cancer cell-derived EVs. Our data show that single colon cancer cells were capable of recruiting and activating platelets and generating fibrin in plasma under shear flow. Finally, in a retrospective analysis of colon cancer patients, we found that the number of venous thromboembolism events was 4.5 times higher in colon cancer patients than in a control population. In conclusion, our data suggest that platelet-cancer cell interactions and perhaps platelet procoagulant EVs may contribute to the prothrombotic phenotype of colon cancer patients. Our work may provide rationale for targeting platelet-cancer cell interactions with PAR4 antagonists together with aspirin and/or ADP receptor antagonists as a potential intervention to limit cancer-associated thrombosis, balancing safety with efficacy.